Implications for public policy - Joyce, Jimmy (Statistical and Social Inquiry Society of Ireland, 1997)
Ladies and Gentlemen, I am grateful to the Society for inviting me to make a contribution to your meeting. My contribution takes the form of some random, but I hope fairly provocative, thoughts on pension related matters. Also, since pensions are a boring old subject, some of my remarks are intended to be a bit tongue in cheek - your task is to work out which.
Symposium on Pensions: Implications for Public Policy
Read before the Society, 13 March 1997
Keywords: Retirement age; Pensions; 314.15